Effect of Application over Time for Each Type of Blending Tea on Bovine Tooth Coloration - Bae, Se-Won; Jung, Im-Hee; Hong, Min-Ha; Kwon, Eun-Jin; Kim, Ji-Hyeon; Lee, Ji-Hyeon; Lim, Hee-Jung; Lim, Do-Seon (Chiwisaeng gwahakoeji, 2022)
Background: This study aimed to investigate the effect of selecting commercially available blending teas and applying them to bovine teeth on color change over time.Methods: After selecting healthy bovine teeth, using a cutting-disc, 105 specimens with a dimension of 5×5×3 mm were prepared, and 15 specimens were distributed to each group. Black tea was used as a positive control, water was used as a negative control, and blended tea of five types was used as an experimental group. First, pH and buffering capacity were measured with a pH meter, and tooth color was determined using a spectrophotometer before immersion in the blending tea solution and 1, 5, 7, 14, and 21 days after immersion. Thereafter, the shape change of the enamel surface was observed using a scanning electron microscope, and SPSS ver.26 was used to analyze the color change.Results: The average pH of the five blending teas in the experimental group was 3.78, and the pH of group 3 (strawberry rhubarb) was the lowest at 3.22. The pH levels of black tea and water were 5.19 and 7.30, respectively. The buffering capacity was the highest in group 3 at both pH levels of 5.5 and 7.0. The L*a*b* color change according to immersion time was the largest in group 4 (rooibos yellow flower), and the amount of color change was large in black tea and group 4. As a result of observing the enamel surface of bovine teeth, changes in the surface shape were noted in all groups immersed in the experimental solution for 21 days, except for water.Conclusion: There was a significant difference between the experimental groups in terms of color change according to the immersion time, and color and enamel surface changes were observed in black tea and all experimental groups, except for water.